Simulasi Statik Pada Polisi Tidur Terbuat dari Beton Busa yang Diperkuat dengan Serat Kulit Durian Menggunakan Software Ansys: Static Simulation on Speed bumps Made of Foam Concrete Reinforced with Durian Leather Fibers Using Ansys Software - Maraghi Muttaqin (YCMM, 2021)
Speed ​​bumps are considered disturbing motorcyclists to increase vehicle speed. The idea was born to develop a tool that can use a power generator with a speed bump generator as a driving source in this application. This product is designed and manufactured on a full scale to cover all speed bump vehicles. Why is that because the vehicle's kinetic energy is stored and converted into electricity which is stored in the battery. In order to obtain a structurally integrated material, the sleeping police carried out several tests, including static and impact tests. Static and impact testing is done by simulation using ansys software. Durian peel is very suitable as a mixture as an ingredient because it contains fiber that can be used for concrete reinforcement. Also obtained the equivalent stress of 0.05 MPa. The x-Axis voltage is 0.01MPa. The y-axis stress is 0.04 MPa. The results of this study can be concluded that the foam concrete composite reinforced with durian skin fiber also has the potential to be used as a speed bump power generator.